'Second generation' Sikh autobiographies and authobiographical novels in European languages: Turning towards and away from traditions. (2nd October 2018) - Jacobsen, Knut A.
ABSTRACT: The article analyzes autobiographies and autobiographical novels by Sikh authors who were born and grew up in Europe and North America as sources for understanding developments of Sikh religion. It uses the concepts panjabiat (Punjabi-ness), Sikh religion and modernity/Western society to understand the tensions and conflicts described in these books. The authors had to work out the differences between panjabiat, Sikh religion and modernity/Western society. They had to figure out what place the Sikh religion should have in their new identity and for this they were looking for similarities between the Sikh religion and Western society. In the autobiographies Sikh religion emerges as an ideology employed to criticize Punjabi culture and society and Sikh religion is reinterpreted and often comes to refer to some general principles that are compatible and supportive of Western modernity.